GAMMA-RAYS AND ETHYL METHANE SULPHONATE INDUCED MUTATION IN MICROSPERMA LENTIL (LENS CULINARIS L. MEDIKUS) - RAM NARAYAN AHIRWAR; JAY PRAKASH LAL; PRAKASH SINGH (The Bioscan, 2014)
Mutagenic sensitivity was studies in the lentil variety HUL-57 (Malavia Vishwanath) by treating the seeds with 10kR, 20kR and 30kR of gamma-rays and chemical 0.3% concentration of ethyl methane sulphonate (EMS) mutagens singly and in combinations of both. Mutagenic treatment showed highly significance differences for all the morphological and yield traits in both of the generations (M1 and M2). The highest reduction in germination (42 %), plant survival (23.85 %), root length (76.4 %) and shoot length (90.22 %) were observed at combine treatment of gamma rays (30 kR) and EMS (0.3%). Root length showed more sensitivity as compared to shoot length. The frequency of chlorophyll mutants was quite narrow as only three types of mutant, viz., albino, xantha and viridis were observed. The induction of Albino (2) mutants was obtained only at 0.3 % EMS, whereas xantha and viridis types of mutants were recorded at all the doses, maximum being at 0.3 % of EMS mutagens. For induction of chlorophyll mutation 0.3 % EMS alone mutagens proved to be the best option. Thus, it may be concluded that the mild doses of mutagens may be more useful to induce desired type of chlorophyll mutants.